Geometric Calibration of a Hyperspectral Frame Camera - de Oliveira, Raquel A. [UNESP]; Tommaselli, Antonio M. G. [UNESP]; Honkavaara, Eija (Wiley, 2016)
Recently, miniaturised hyperspectral sensors operable from small unmanned airborne vehicle platforms have entered the market. The emerging hyperspectral imaging technologies, based on frame cameras and tuneable filters, are attractive alternatives to hyperspectral pushbroom sensors. This paper addresses the geometric calibration process of a hyperspectral frame camera based on a Fabry–Pérot interferometer. However, the addition of more optical elements in front of the image sensor can affect the parameters related to the internal geometry of the camera, and a deficiency in knowledge regarding these parameters can have a critical effect on the accuracy of 3D measurements in photogrammetric applications. The experiments focused on assessing the self-calibrating bundle adjustment to verify the behaviour of the interior parameters, considering different spectral bands. The results indicated that the applied self-calibration method can accurately characterise the interior parameters of this camera and that one set of parameters is required for each internal sensor.
Keywords: camera calibration; Fabry–Pérot interferometer; hyperspectral frame camera; photogrammetry; tuneable filters